Gender Diversity and Inclusiveness in the Valuation Surveying Discipline: Examining Workforce Composition and the Influence of Organisational Policies in Uganda - Mugalu, Charles; Barasa, Linda (Journal of African Real Estate Research, 2025)
This study investigated the gender composition within Uganda’s valuation surveying discipline. It examined the influence of organisational policies on this composition through a mixed-methods explanatory sequential research design. Initially, quantitative data were gathered through a desk review, followed by the collection and analysis of qualitative data obtained from semi-structured interviews with representatives of valuation surveying firms affiliated with registered valuation surveyors of Uganda. The study’s findings revealed a significant underrepresentation of women in Uganda’s valuation surveying discipline, with women comprising only 22% compared to 78% of men. This disparity is attributed to educational barriers, stereotypes, and organisational barriers that have considerably affected women’s participation in the profession relative to men. The findings contribute to the broader discourse on gender equity in STEM fields, offering insights pertinent to promoting a gender-inclusive valuation surveying profession in alignment with global efforts to achieve gender equality and women’s empowerment, as outlined in Goal 5 of the Sustainable Development Goals.